Best. Night. Ever : a story told from seven points of view - Malone, Jen; Alpine, Rachele, 1979-; Arno, Ronni; Cherry, Alison; Faris, Stephanie; Nall, Gail; Romito, Dee (Aladdin, 2017)
On the night of a middle school dance, excitement yields to complications for seven students, some who perform with their rock band, some who attend, and some who have other obligations.